1964
DOI: 10.1099/00221287-35-3-459
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Degradation of the Ferrichrome Compounds

Abstract: SUMMARYAn unidentified Pseudomonas capable of growth on ferrichromes as sole sources of carbon and nitrogen was isolated by enrichment culture on ferrichrome A. The spectral shifts observed for the culture supernatant fluids and the degradation products which accumulated in the culture media during growth on these compounds indicated that initially the cyclic peptide rings are broken to yield simpler hydroxamates. These simpler hydroxamates were then deacylated, perhaps after reduction to the corresponding N-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1971
1971
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Earlier reports on the occurrence of siderophore degrading bacteria have shown that strains of Pseudomonas were able to split hexapeptide siderophores of the ferrichrome family (Warren & Neilands 1964, 1965. Pseudomonas FC-1 was isolated from soil by enrichment culture on ferrichrome A as sole source of carbon and nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier reports on the occurrence of siderophore degrading bacteria have shown that strains of Pseudomonas were able to split hexapeptide siderophores of the ferrichrome family (Warren & Neilands 1964, 1965. Pseudomonas FC-1 was isolated from soil by enrichment culture on ferrichrome A as sole source of carbon and nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Neilands and colleagues (33)(34)(35) observed that their microbe, named Pseudomonas FC1, degraded the hydroxamate siderophores ferrichrome, ferrichrome A, and coprogen, with ferrichrome A being the most facile to degrade. Pseudomonas FC1 siderophore degradation was due to inducible enzymes and could occur with either the deferrisiderophore or the ferrisiderophore.…”
mentioning
confidence: 99%
“…Three siderophore-degrading microbes, a pseudomonad (33)(34)(35), Azospirillum irakense (36,37), and Mesorhizobium loti (4,7,17,39), catabolize siderophores concomitant with their growth. Neilands and colleagues (33)(34)(35) observed that their microbe, named Pseudomonas FC1, degraded the hydroxamate siderophores ferrichrome, ferrichrome A, and coprogen, with ferrichrome A being the most facile to degrade.…”
mentioning
confidence: 99%
“…A microbe employing such a strategy would thus be prevented from denying itself a source of Fe 3+ due to the use of either the ferrisiderophore or the deferrisiderophore as a carbon source. While DFBC 5 displays the nutritional selectivity of not using the same siderophore as both a source of carbon and iron, the only other organism reported as being capable of siderophore catabolism, a bacterium termed Pseudomonas FC 1 (Warren & Neilands 1964), dissimilated both the ferri and deferrated forms of ferrichrome and ferrichrome A (Warren & Neilands 1964). While not displaying an ability to metabolize siderophores or hydroxamic acid compounds in general, Pseudomonas FC1 used ferrichrome, ferrichrome A, deferriferrichrome, deferriferrichrome A and, to a limited extent, ferric coprogen as carbon sources.…”
Section: Discussionmentioning
confidence: 99%
“…Little attention, however, has been focused on how siderophores are recycled into the carbon cycle. Only two microbial isolates, one a soil pseudomonad which metabolized ferrichrome A and ferrichrome (Warren & Neilands 1964, Villavicencio & Neilands 1965, Warren & Neilands 1965, and the other a Gram-negative rod of uncertain taxonomic identity which catabolized deferrioxamine B (DFB) (Castignetti & Siddiqui 1990), have been noted to efficiently use siderophores as sole sources of carbon for growth.…”
Section: Introductionmentioning
confidence: 99%